Targeting arterial partial pressure of carbon dioxide in acute respiratory distress syndrome patients using extracorporeal carbon dioxide removal. Issue 4 (29th November 2021) - Leypoldt, John K.; Kurz, Jörg; Echeverri, Jorge; Storr, Markus; Harenski, Kai
Abstract: Background: A retrospective analysis of SUPERNOVA trial data showed that reductions in tidal volume to ultraprotective levels without significant increases in arterial partial pressure of carbon dioxide (PaCO2 ) for critically ill, mechanically ventilated patients with acute respiratory distress syndrome (ARDS) depends on the rate of extracorporeal carbon dioxide removal (ECCO2 R). Methods: We used a whole‐body mathematical model of acid‐base balance to quantify the effect of altering carbon dioxide (CO2 ) removal rates using different ECCO2 R devices to achieve target PaCO2 levels in ARDS patients. Specifically, we predicted the effect of using a new, larger surface area PrismaLung+ device instead of the original PrismaLung device on the results from two multicenter clinical studies in critically ill, mechanically ventilated ARDS patients. Results: After calibrating model parameters to the clinical study data using the PrismaLung device, model predictions determined optimal extracorporeal blood flow rates for the PrismaLung+ and mechanical ventilation frequencies to obtain target PaCO2 levels of 45 and 50 mm Hg in mild and moderate ARDS patients treated at a tidal volume of 3.98 ml/kg predicted body weight (PW). Comparable model predictions showed that reductions in tidal volumes below 6 ml/kg PBW may be difficult for acidotic highly severe ARDS patients with acute kidney injury and high CO2 production rates using a PrismaLung+ device in‐series with a continuous venovenous hemofiltration device. Conclusions: The described model provides guidance on achieving target PaCO2 levels in mechanically ventilated ARDS patients using protective and ultraprotective tidal volumes when increasing CO2 removal rates from ECCO2 R devices. Abstract : The described mathematical model predicts the extracorporeal carbon dioxide (CO2 ) removal rate to achieve target arterial partial pressure of carbon dioxide (PaCO2, in mmHg) in mild and moderate acute respiratory distress syndrome patients for various respiratory frequencies at ultraprotective mechanical ventilation tidal volumes (4 mL/kg PBW).